2020
DOI: 10.1111/ssqu.12791
|View full text |Cite
|
Sign up to set email alerts
|

Do the Affluent Override Average Americans? Measuring Policy Disagreement and Unequal Influence

Abstract: Objective. In this article, I seek to adjudicate between contradictory findings in studies of unequal responsiveness that focus on policy issues over which affluent and average Americans disagree. Methods. I assess the impact of 22 definitions of policy disagreement and two methods of measuring policy influence-based on win rates and policy change rates-on analyses of unequal responsiveness. Results. Win rates are an unreliable measure of influence and comparing policy change rates across cases of agreement an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…See Bashir (2015), Enns (2015), and Branham et al (2017). Bowman (2020) has extensively tested these possibilities and found that the main alternative—win rates for subgroups—is inconsistent across different definitions of disagreement and heavily affected by status quo bias. We also present results that consider status quo bias.…”
mentioning
confidence: 99%
“…See Bashir (2015), Enns (2015), and Branham et al (2017). Bowman (2020) has extensively tested these possibilities and found that the main alternative—win rates for subgroups—is inconsistent across different definitions of disagreement and heavily affected by status quo bias. We also present results that consider status quo bias.…”
mentioning
confidence: 99%
“…Nevertheless, this article sheds further light on the detrimental effects of inequality on democracy. A primary function of elections is the distribution of power and mounting American evidence demonstrates their governments are far more responsive to the wealthy over everyone else (Bartels, 2008;Bowman, 2020;Gilens, 2012;Hacker & Pierson, 2010). It would appear from this study that Canada is treading down a similar path to its southern neighbor.…”
Section: Resultsmentioning
confidence: 99%
“…Mounting evidence also demonstrates that governments are far more responsive to the wealthy over everyone else (Bartels, 2008;Bowman, 2020;Gilens, 2012;Hacker & Pierson, 2010;Schakel, 2019). Thus, the nature of the relationship between income inequality and voting is important because widening income inequality can concentrate political and decision-making power in the hands of a few.…”
Section: Introductionmentioning
confidence: 99%
“…Representatives often respond more to wealthy citizens, interest groups, and members of their own political parties than to the public writ large (Bartels 2008;Gilens 2012;Gilens and Page 2014;Lax, Phillips, and Zelizer 2019;Stokes 2020). After controlling for affluent Americans' and interest groups' preferences, scholars do not find a relationship between the middle class's preferences and public policy decisions (Gilens and Page 2014;Bowman 2020). Representatives are also more likely to be responsive to non-minority than minority constituents (Butler and Broockman 2011;Broockman 2013;Butler 2014;Costa 2017), a bias that cannot be explained by the demographic composition of representatives' districts (Einstein and Glick 2017;Mendez and Grose 2018).…”
Section: The Mechanisms Of Representationmentioning
confidence: 99%